Barriers and facilitators to utilizing HIV prevention and treatment services among migrant youth globally: A scoping review. - Kevin Li; Natasha Thaweesee; Allison Kimmel; Emily Dorward; Anita Dam (PLOS Global Public Health)
Both migrants and young people experience disproportionately high rates of HIV acquisition and poor access to HIV prevention and treatment services. To develop effective interventions and reach epidemic control, it is necessary to understand the barriers and facilitators to accessing HIV services among migrant youth. We conducted a scoping review to identify these factors for migrant youth ages 15-24, globally. We conducted a PRISMA-concordant scoping review using keyword searches in PUBMED and Web of Science for peer-reviewed primary literature published between January 2012 and October 2022. We included studies that investigated barriers and facilitators to accessing services for migrant youth participants. We used the Socio-Ecological Model as an analytical framework. The 20 studies meeting the inclusion criteria spanned 10 countries, of which 80% (n = 16) were low- and middle-income countries. Study methods included were quantitative (40%), qualitative (55%), and mixed methods (5%). Six studies included refugee youth (30%), 6 included migrant worker youth (30%), 3 included immigrant youth (15%), 2 included rural migrant youth (10%), and 1 included immigrants and refugees. The remainder represented unspecified migrant youth populations (10%). At the individual level, education level and fear of infection acted as barriers and facilitators to HIV services. At the relationship level, social support and power in relationships acted as barriers and facilitators to HIV services. At the community level, barriers to HIV services included discrimination and stigma, while community and religious outreach efforts facilitated access to HIV services. At the structural level, barriers to HIV services included stigmatizing social norms, lack of health insurance, and legal barriers. Migrant youth face significant, unique barriers to accessing HIV services. However, facilitators exist that can be leveraged to enable access. Future implementation science research, enabling policies, and adapted programmatic interventions should prioritize migrant youth as a distinctive sub-population to receive targeted HIV services.